The Impact of Drill Exercise and Games Approach on Improving Under-Passing Ability in Adolescent Female Volleyball Athletes - Dwi Khoirudin; Henri Gunawan Pratama; Danang Ari Santoso; Baskoro Nugroho Putro (Physical Education and Sports: Studies and Research, 2023)
Background: A long-term training process is required to train athletes, which requires systematic, targeted, planned, and repetitive handling. Training methods improve the mastery of fundamental techniques for beginner athletes. Training volleyball methods are essential for beginners as they make the exercise more focused and gradual to improve their under-passing. Coach training methods make it easier to give practical and concentrated exercises to the areas you want to enhance. Objective: The study aims to determine whether drill exercise and game approach can significantly improve female athletes' use of under-passing volleyball. Methods: With the type of research being Quasi-Experimental. The research design used was Randomized Control Group Pretest-Posttest Design. A total of 24 athletes were given treatment for two months. The instrument used was the Braddy Volleyball Test, and data analysis used the T-Test. Results: Results for the drill exercise experimental group were 0.695 > 0.05, and for the experimental group, the playing method was 0.695 > 0.05. This means that drill exercises and game approaches significantly improve the skills of passing volleyball. Conclusion: In experimental groups, I and II, athletes who were given a drill exercise program and game approach both improved their skills in the basic techniques of skills under-passing volleyball. The average posttest results of both groups of experiments are higher than the average pretest results. It shows a difference between the drill exercise program and the game approach.